MiR-3664-3p through suppressing ABCG2, CYP3A4, MCL1, and MLH1 increases the sensitivity of colorectal cancer cells to irinotecan - Elham Farrokhnazar; Sahar Moghbelinejad; Reza Najafipour; Ladan Teimoori-Toolabi (Heliyon)
Background: Colorectal cancer (CRC) is the third most frequently diagnosed malignancy worldwide. Currently, irinotecan (CPT-11) is used alone or in combination with other drugs to treat patients with advanced CRC. However, the 5-year survival rate for metastatic CRC remains below 10 %, largely due to chemotherapy resistance. Several genes, including ABCG2, CYP3A4, MCL1, and MLH1 contribute to irinotecan resistance. This study aimed to identify microRNAs that simultaneously regulate the expression of these genes in irinotecan-resistant cell lines and study their effect on resistant colorectal cancer cells. Methods: Irinotecan-resistant colorectal cancer cell lines were developed by intermittently exposing HCT116 and SW480 cell lines to gradually increasing doses of irinotecan over four generations. These resistant cell lines were designated HCT116-R1, HCT116-R2, HCT116-R3, HCT116-R4 and SW480-R1, SW480-R2, SW480-R3, SW480-R4. The induction of resistance was confirmed using MTT assays, by calculating IC50 values for each generation and comparing them to the parental cells. The expression levels of the ABCG2, CYP3A4, MCL1, and MLH1 genes, along with miR-3664-3p, were initially measured in all resistant and parental cell lines using quantitative real-time PCR. Following transfection of HCT116-R3 and SW480-R3 cells with pre-miR-3664-3p, the expression levels of ABCG2, CYP3A4, MCL1, MLH1, and miR-3664-3p were re-evaluated using real-time PCR. Results: In resistant cell lines derived from HCT116 and SW480, increased expression of the ABCG2, CYP3A4, and MCL1 genes was observed. However, a reduction in CYP3A4 expression was noted in the final resistant lines from both cell lines. Additionally, while MLH1 expression increased in HCT116-derived cell lines, no significant increase was observed in SW480-derived lines. A consistent decrease in miR-3664-3p expression was found across all resistant cell lines. When we transfected HCT116-R3 and SW480-R3 cells with pre-miR-3664-3p, there was an increase in miR-3664-3p expression and a reduction in ABCG2, CYP3A4, MCL1, and MLH1 gene expression. This led to increased sensitivity to irinotecan. Conclusion: It can be concluded that miR-3664-3p can be considered a regulator of resistance to irinotecan by modulating the expression of ABCG2, CYP3A4, MCL1, and MLH1 genes.